Radiation characteristics of an aerogel-supported fission fragment rocket engine for crewed interplanetary missions - Weed, Ryan; Duncan, R. V.; Horsley, Matthew; Chapline, George (Frontiers in Space Technologies, 2023)
The ionizing radiation properties of a fission fragment rocket engine concept are described in the context of a crewed Mars mission. This propulsion system could achieve very high specific impulse (>10 6 sec) at high power density (>kW/kg), utilizing micron-sized fissile fuel particles suspended in an aerogel matrix. The fission core is located within the bore of an electromagnet and external neutron moderator material. The low-density aerogel allows for radiative cooling of fuel particles while minimizing collisional losses with the fission fragments, leading to more efficient use of fissile fuel in producing thrust compared to previous concepts. This paper presents estimates of the steady state ionizing radiation equivalent dose to the astronaut crew from both external (e.g. galactic cosmic rays) and internal (reactor) sources. The spacecraft design includes a centrifugation concept where the transit habitation module rotates around the spacecraft center of mass, providing artificial gravity to the crew and separation distance to the nuclear core. We find that the fission fragment propulsion system combined with centrifugation could lead to reduced transit time, reduced equivalent radiation dose, and reduced risk of long-term exposure to micro-g environments. Such a high specific impulse propulsion system would enable other crewed fast transit, high delta-V interplanetary missions with payload mass fractions much greater than alternative propulsion architectures (chemical, solarelectric)